Gallantry and Matrimonial Heterosexuality: Love and Friendship in Scudéry's Carte de Tendre (1654). (2nd April 2020) - Dupas, Matthieu
ABSTRACT: This article reads Scudéry's Carte de Tendre from the viewpoint of the history of sexuality. Scholars have argued that Scudéry's map, by implementing a reconfiguration of emotions, paves the way for modern affective subjectivity. I suggest that by virtue of a deferral of sex typical of gallantry, the Carte de Tendre pictures a tension between two economies of feelings in relation to sex: two erotics . While drawing on a homoerotic conception of friendship — redefined as "tender friendship" once women are given access to it — the map points to a modern de-eroticized, or heterosocial, definition of friendship in contrast with (hetero)sexual love. It suggests that the access of women to friendship in seventeenth-century France has played an important role in the development of sexuality as a heteronormative apparatus in the modern era.